KETEPATAN PEMBERIAN OPINI AUDITOR : SURVEY TERHADAP AUDITOR DI YOGYAKARTA - Abriyani Puspaningsih; Noeroel Fadlilah (Jurnal Aplikasi Bisnis, 2018)
This study aims to examine the accuracy of giving opinion by the auditor. Factors that are expected to have an effect on the accuracy of the auditor's opinion are professional skepticism, experience, audit situation, expertise and workload. This research was conducted by survey method using questionnaires distributed to auditors working in the public accounting firm in Yogyakarta. The sampling technique using a random sampling. The results showed that the variables of professional skepticism and audit situation has significant positive effect on the accuracy of giving opinions by the auditor. There are three variables that do not have a significant effect on the accuracy of giving the auditor's opinion in this study, namely the experience, expertise, and workload. This is because the auditors who were respondents in this study are mostly junior auditor, with an educational background S1 is still a bit of experience, expertise and workload.